Strategi Deradikalisasi pada Anak Usia Dini Berbasis Pendidikan Ahlussunah Waljamaah - Ari Masrokhah; Yenny Aulia Rachman; Triana Hermawati (At Turots: Jurnal Pendidikan Islam, 2022)
The purpose of this study was to determine the importance of implementing a deradicalization strategy in PAUD ELPIST Temanggung and to describe the implementation of a deradicalization strategy based on ahlus sunnah wa al-jama'ah education in PAUD ELPIST Temanggung. This study discusses the education of ahlus sunnah wa al-jama'ah which is used as a deradicalization strategy. This research focuses on habituation to children by instilling the value of ahlus sunnah wa al-jama'ah, which is carried out every day. This research is a qualitative research with the object of deradicalization strategy based on ahlus sunnah wa al-jama'ah education. Data was collected by means of interviews, observations and documentation conducted at PAUD ELPIST Temanggung. In this study, researchers used field research (field research). Then the collected data will be analyzed using in-depth analysis of a content in the form of documented information.